b - Katsikas, Sokratis K.; Sideridis, Alexander B.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the refereed proceedings of the 6th International Conference on E-Democracy, E-Democracy 2015, held in Athens, Greece, in December 2015. The 13 revised full papers presented together with 8 extended abstracts were carefully selected from 33 submissions. The papers are organized in topical sections on privacy in e-voting, e-polls and e-surveys; security and privacy in new computing paradigms; privacy in online social networks; e-government and e-participation; legal issues. The book also contains the extended abstracts describing progress within European research and development projects on security and privacy in the cloud; secure architectures and applications; enabling citizen-to-government communication.
Keywords: Computer science; Computer security; Information Systems; Computers and Society; Systems and Data Security; Management of Computing and Information Systems; Information Systems Applications (incl. Internet).